Rabies eradication measures in wildlife in the Republic of Moldova - Maxim SIRBU (Asociatia de Biosiguranta si Biosecuritate, 2021)
Introduction. Rabies is one of the most dangerous zoonoses in the world with a lethality rate around 100% of infected animals. The main factor in rabies’ control is the prophylactic immunization of domestic and wild carnivores.